2019
DOI: 10.1007/s12220-019-00213-3
|View full text |Cite
|
Sign up to set email alerts
|

Second-Order Regularity for Parabolic p-Laplace Problems

Abstract: Optimal second-order regularity in the space variables is established for solutions to Cauchy-Dirichlet problems for nonlinear parabolic equations and systems of p-Laplacian type, with square-integrable right-hand sides and initial data in a Sobolev space. As a consequence, generalized solutions are shown to be strong solutions. Minimal regularity on the boundary of the domain is required, though the results are new even for smooth domains. In particular, they hold in arbitrary bounded convex domains.Here, p >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…As a consequence, he also observed that the time derivative u t exists and belongs to a Sobolev space. See also a recent paper by Cianchi and Maz'ya [5].…”
Section: Dumentioning
confidence: 99%
“…As a consequence, he also observed that the time derivative u t exists and belongs to a Sobolev space. See also a recent paper by Cianchi and Maz'ya [5].…”
Section: Dumentioning
confidence: 99%
“…We refer to the classical results by DiBenedetto [20], Gilbarg and Trudinger [26], Ladyžhenskaja et al [28,29], Liebermann [30], Uhlenbeck [40], Ural'ceva [41], just to cite a few; or the ones linked more to applications Bensoussan and Frehse [9], Nečas [34], and Fuchs and Seregin [24]. Even if the studies started in the sixties, we observe that the field is still extremely active and very recent results are those in [3,4,17,18].…”
Section: Introductionmentioning
confidence: 71%
“…It is shown that u t ∈ L 2 (Q T ) and |∇u| p−2 ∇u ∈ W 1,2 (Q T ), provided that f ∈ L 2 (Q T ) and u 0 ∈ L 2 (Q T ) ∩ W 1,p 0 (Ω). This regularity result is sharp -see [22,Remark 2.3]. It is worth noting here that the use of Galerkin's approximations prevents one from employing the techniques developed in these works.…”
Section: Introductionmentioning
confidence: 94%
“…The stronger result on the differentiablity of the flux is obtained in [22]. It is shown that u t ∈ L 2 (Q T ) and |∇u| p−2 ∇u ∈ W 1,2 (Q T ), provided that f ∈ L 2 (Q T ) and u 0 ∈ L 2 (Q T ) ∩ W 1,p 0 (Ω).…”
Section: Introductionmentioning
confidence: 94%